Cervical Cancer with Radiotherapy Treatment - Novita Ariani; Herli, Muhammad Azhari; Laila, Nurul (As-Shiha: Jurnal Kesehatan, 2024)
Cervical cancer is an abnormal growth of cells in the cervix, which its etiological agent is infected by the human papillomavirus. Globally, cervical cancer is the fourth most common cancer in women, one of the most frequently diagnosed cancer, and a cause of cancer-related death. The Global Cancer Statistics 2022, censused approximately 660,000 new cases and 350,000 deaths worldwide. Therefore, to contrast cervical cancer as a public health problem, the World Health Organization in 2020, conducted a global health strategy with tertiary interventions: (1) prevention through HPV vaccination; (2) screening and precancerous lesions treatment; and (3) adequate treatment of invasive cervical. Currently, there are three therapeutic modalities which are surgery, chemotherapy, and radiotherapy. These may include one or a combination of surgery, chemotherapy and radiotherapy. Radiotherapy is a major treatment in the management of cervical cancer, which uses high energy x-rays.